The Case of the POTRAIT VANDAL - Brezenoff, Steven (MUSEUM MYSTERIES, 2015)
Somebody is vandalizing exhibits at the Capitol City Museum of American History, and it is up to twelve-year-old Raining Sam and his friends to find the culprit before irreparable damage is done